Early assessment of the severity of asphyxia in term newborns using parameters of blood count - Brucknerová, Ingrid (Slovak Toxicology Society SETOX, 2008)
Acute perinatal asphyxia is a major cause of death and neurological injury in newborn infants. Severe asphyxia can occur in infants around the time of birth for several reasons. The aim of our study was to find the most sensitive, easily obtainable and fast assessable parameter of the presence and quantification of asphyxia. In our study 39 term newborns (15 healthy term newborns and 24 asphyxial term newborns), from vaginal deliveries admitted within 24 hours of life were monitored and parameters of blood count from venous blood were assessed. Laboratory findings of blood count parameters revealed significant differences between term asphyxial and healthy newborns in erythrocyte count and hemoglobin and hematocrit values. Hematological changes observed early after delivery can determine the duration of hypoxemia (acute vs. chronic) and asphyxia of short duration may be accompanied without occurrence of polyglobulia.